FAKTOR RISIKO GIZI KURANG PADA BALITA DI WILAYAH KERJA PUSKESMAS PURI KABUPATEN MOJOKERTO - Asih Media Yuniarti; Elyana Mafticha; Diana Narika Sari; Mukhammad Himawan Saputra (STIKes Al-Insyirah Pekanbaru, 2022)
Nutritional status is the main source for determining the growth and development of a person's body, especially in toddlers. Malnutrition can have an unavoidable adverse impact, where the worst manifestations can lead to death. The purpose of this study was to determine the risk factors for undernutrition in toddlers in Puskesmas Mojokerto Regency. This research method used the observational method with a cross-sectional research design and used the chi-square test with a sample of 92 respondents. Data collection was carried out using a questionnaire and a 24-hour food recall. This research was conducted in August 2022. The results showed that most of the toddlers received adequate food intake (53.3%), most of the toddlers had experienced infectious diseases (52.2%), and most of the toddlers had malnutrition status ( 53.3%). The results of the Chi-Square test showed that the variables that had a significant relationship with malnutrition in toddlers, were food intake (p = 0.000) and infectious diseases (p = 0.000). The food intake consumed by toddlers is very monotonous so it makes them have no appetite and causes food intake to be unfulfilled, while in infectious diseases most toddlers who have experienced diarrhea, coughs, colds, and fever greatly affect malnutrition in toddlers. It is hoped that the health service and nutrition program holders can increase socialization and provide health education, especially on how to provide good nutrition to toddlers continuously so that they are not susceptible to infectious diseases